2020
DOI: 10.1007/s00508-019-01597-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated eyesight and handgrip strength in older adults

Abstract: Background:The aim of this study was to investigate the association between self-rated eyesight and handgrip strength in a large, representative population of older adults.Methods: Data were from 7,433 older adults (≥52y) participating in the English Longitudinal Study of Ageing. We used linear regression to analyse the association between self-rated eyesight and handgrip strength cross-sectionally in 2004/05, and longitudinally over four-year follow-up, adjusting for a range of socio-demographic and health-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…The association between sensory organ function and LHGS demonstrated a progressively increasing pattern as visual and hearing acuity deteriorated. Our results are similar to those of previous research that poor self-rated eyesight was associated with LHGS, and multiple sensory impairments, including hearing impairment, were associated with lower adjusted mean handgrip strength [ 23 , 24 ]. However, prior studies only divided visual and hearing acuity in a dichotomous manner to evaluate the association with handgrip strength, and there was no study in which hearing impairment alone was related to LHGS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The association between sensory organ function and LHGS demonstrated a progressively increasing pattern as visual and hearing acuity deteriorated. Our results are similar to those of previous research that poor self-rated eyesight was associated with LHGS, and multiple sensory impairments, including hearing impairment, were associated with lower adjusted mean handgrip strength [ 23 , 24 ]. However, prior studies only divided visual and hearing acuity in a dichotomous manner to evaluate the association with handgrip strength, and there was no study in which hearing impairment alone was related to LHGS.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the functional connection between sensory and motor areas [ 22 ], little is known about the relationship between visual and hearing acuity, muscle weakness, and low muscle mass, which is an important cause of the decrease in physical function [ 4 , 23 , 24 ]. Sensory function is an indicator of healthy physical aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing our second objective, our study documents in six middle-income countries, a robust and comprehensive association of handgrip strength with measures of intrinsic capacity. These correspond to each of the five important domains identified by WHO: locomotion, psychological, vitality and cognitive capacity supporting the findings of previous fragmented studies 12 14 , 17 , 45 , 46 . For example, a study conducted among older adults aged 60 and above in Colombia showed significant association between handgrip strength and measures of intrinsic capacity such as vitality, sensory, cognition, and psychological capacities 13 .…”
Section: Discussionsupporting
confidence: 86%
“…For example, a study conducted among older adults aged 60 and above in Colombia showed significant association between handgrip strength and measures of intrinsic capacity such as vitality, sensory, cognition, and psychological capacities 13 . Our findings of inverse association of handgrip strength with depressive disorders, sensory impairments, and positive association with measures of cognition and gait speed are also consistent [12][13][14]17,45,46 .…”
Section: Discussionsupporting
confidence: 80%